Procesos comunitarios en la vialidad rural Una guía metodológica - Pérez Carrillo, Yolanda (Editorial Universidad Nacional (EUNA), 2020)
This Methodological Guide is the result of the participatory processes carried out from the university extension with the communities of the Canton of Naranjo. It seeks to guide in a pedagogical way, the various processes that the communities must develop within the groups, which lead the community processes in the field of rural roads.